Simultaneous nitrogen and sulfur removal using Anammox coupled sulfide-denitrification process: Impact of pH. (October 2022) - Ma, Bingbing; Zhang, Xiaojing; Wei, Denghui; Ma, Yongpeng; Wang, Qiong; Zhang, Han; Zhang, Jiajie
Abstract: Nitrogen and sulfur coexisted in many kinds of wastewaters, which could be simultaneously removed in the Anammox coupled sulfide-denitrification process. In this study, the pH suitable for the coupling process was analyzed in a biofilter. The results showed that the coupling process could operate normally at pH of 6.5–8.5, with the total nitrogen removal efficiency (TNRE) higher than 85.0 %. At pH 7.5, the TNRE reached the highest, the hydroxylamine oxidoreductase (HAO) activity and heme-c reached 0.998 EU·g −1 SS and 0.0010 mmol·g −1 SS, respectively, with the hzo and nosZ gene concentrations as 4.6 × 10 8 and 9.7 × 10 7 copies·mL −1 . At pH 6.0, the process was significantly deteriorated and it secreted more protein to resist the pH shock, the TNRE was 34.0 %, HAO, hzo and nosZ genes and abundance of Candidatus_Kuenenia decreased by 2.8, 4.2, 2.2, and 1.4 times, respectively. Thiobacillus reduced nitrate to nitrite and supplied for Candidatus_Kuenenia, but utilized nitrite in adverse environment. Graphical abstract: Unlabelled Image Highlights: The Anammox coupled sulfide-denitrification process could run normally at pH 6.5–8.5. Simultaneous nitrogen and sulfur removal was achieved using the coupling process. The nitrogen removal, HAO, hzo and nosZ genes all decreased under low pH (6.0). The secretion of heme-c increased in harsh environment. The pH decrease from 7.5 to 6.5 mainly inhibited sulfide-denitrification.